Band structure modulation by methoxy-functionalization of graphene nanoribbons. Issue 11 (2nd March 2022) - Götz, Alicia; Wang, Xiao-Ye; Ruini, Alice; Zheng, Wenhao; Soltani, Paniz; Graf, Robert; Tries, Alexander; Li, Juan; Palma, Carlos-Andres; Molinari, Elisa; Hansen, Michael Ryan; Wang, Hai I.; et al.
Abstract : Graphene nanoribbons functionalized with methoxy groups were synthesized. Theoretical studies predicted reduced bandgap and effective mass of charge carriers. THz spectroscopy revealed ∼25% enhancement of the photoconductivity. Abstract : Graphene nanoribbons (GNRs) are considered as potential candidates for next-generation electronic materials, and chemical functionalization can be an efficient method to modulate their electronic properties. This work presents a solution synthesis of methoxy-substituted GNRs through the Diels–Alder polymerization of a tetraphenylcyclopentadienone-based monomer bearing four methoxy groups, followed by oxidative cyclodehydrogenation. The methoxy-functionalization of the GNRs was unambiguously validated by FTIR and solid-state NMR analyses. Moreover, theoretical studies by ab initio calculations predicted both charge redistribution and structural distortion induced by the methoxy substitution, revealing reduction of both the bandgap and of the effective mass of charge carriers. Employing THz spectroscopy, we found that methoxy-substitution at the edges enhanced the photoconductivity of GNRs by a factor of ∼25%, primarily due to the reduced charge effective mass.